The Effectiveness of Using Mind Maps Through Power Point Media in Vocabulary Learning: An Experimental Study at Al-Murshidiyah Islamic Elementary School - Nadhilah Khairina Pulungan; Maswani; Fatimah El Zahra (Penerbit Minhaj Pustaka, 2026)
This study originates from the problem of students’ weak mastery of Arabic vocabulary, as they struggle to memorize vocabulary and understand its meanings due to the use of traditional methods that lack visual and interactive media. To address this issue, the study aims to determine the effect of using mind maps based on PowerPoint media in improving students’ Arabic vocabulary acquisition. It seeks to answer two main questions: how students’ vocabulary learning outcomes improve after using mind maps through PowerPoint, and whether there is a statistically significant effect of using such mind maps on students’ vocabulary acquisition. The researcher employed an experimental method with a quantitative approach using a Non-Equivalent Control Group Design, with a sample of 64 sixth-grade students at Al-Mursyidiyah Islamic Elementary School divided into experimental (32 students) and control (32 students) groups. Data were collected through pre-tests and post-tests and analyzed using normality and homogeneity tests as well as an independent t-test via SPSS. The results showed that the mean score of the experimental group increased from 60.46 to 82.03, while the control group’s mean score rose from 58.12 to 72.03, and the t-test indicated statistically significant differences at the Sig. < 0.05 level.